An Evaluation Of Acupuncture As A Modality Of Treatment Of Leprous Neuritis - Chattopadhyay S P; Neogi Bidisa Guha (Wolters Kluwer Medknow Publications, 1995)
Eighty patients of leprosy who developed peripheral neuritis as a presenting feature or during the course of antileprotic trearment were selected for the study. Groups 1,2,3(N= 20 each) were given acupuncture therapy and considered as acupuncture group . Twenty patients were used as control (Group 4). Patients in acupuncture group showed improvement in subsidence of neural plain and tenderness after ten sittings of acupuncture. The response was best when acupuncture was given as adjunct to antireaction drugs. Relapse rates in Gr. 1, 2, 3 and 4 were 20, 30, 10 and 40 percents respectively. However the effect of acupuncture was temporary and on statistical analysis it was not considered significant when taken as a whole (acupuncture group). Hence acupunture is only recommended where corti- costeroids/NSAIDS are contraindicated. In view of AIDS and Hepatitis B infection, all cases are advised to be screened before acupuncture therapy and the acupuncture needles are autoclaved.